Cytomegalovirus-Associated Inhibition of Hematopoiesis Is Preventable by Cytoimmunotherapy With Antiviral CD8 T Cells - Renzaho, Angelique; Podlech, Jürgen; Kühnapfel, Birgit; Blaum, Franziska; Reddehase, Matthias J.; Lemmermann, Niels A. W. (Frontiers in Cellular and Infection Microbiology, 2020)
Reactivation of latent cytomegalovirus (CMV) in recipients of hematopoietic cell transplantation (HCT) not only results in severe organ manifestations, but can also cause “graft failure” resulting in bone marrow (BM) aplasia. This inhibition of hematopoietic stem and progenitor cell engraftment is a manifestation of CMV infection that is long known in clinical hematology as “myelosuppression.” Previous studies in a murine model of sex-chromosome mismatched but otherwise syngeneic HCT and infection with murine CMV have shown that transplanted hematopoietic cells (HC) initially home to the BM stroma of recipients but then fail to further divide and differentiate. Data from this model were in line with the hypothesis that infection of stromal cells, which constitute “hematopoietic niches” where hematopoiesis takes place, causes a local deficiency in essential hematopoietins. Based on this understanding, one must postulate that preventing infection of stromal cells should restore the stroma's capacity to support hematopoiesis. Adoptively-transferred antiviral CD8+ T cells prevent lethal CMV disease by controlling viral spread and histopathology in vital organs, such as liver and lungs. It remained to be tested, however, if they can also prevent infection of the BM stroma and thus allow for successful HC engraftment. Here we demonstrate that antiviral CD8+ T cells control stromal infection. By tracking male donor-derived sry+ HC in the BM of infected female sry− recipients, we show the CD8+ T cells allow for successful donor HC engraftment and thereby prevent CMV-associated BM aplasia. These data provide a further argument for cytoimmunotherapy of CMV infection after HCT.